The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ol.2018.9084
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal effect of radiation on lymph node metastasis in esophageal carcinoma: A case report and literature review

Abstract: The Abscopal effect is a rare phenomenon observed in the treatment of metastatic cancer, where localized irradiation causes a response in non-irradiated tumor sites. Due to the recent success of immunotherapies, the Abscopal effect of radiation therapy has received renewed clinical interest. However, there is limited knowledge regarding the Abscopal effect and radiotherapy treatment of patients with esophageal carcinoma. The present study reports the case of a 65-year-old male patient, who presented with esoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…The abscopal effect was mostly expected during the treatment of these tumors. In our review, remarkable abscopal responses were also seen in other histologic types, such as gastric, esophageal, or pancreatic cancers [17,[21][22]. This observation is consistent with preclinical data, suggesting that the combination of RT and immunotherapy induces effective immune responses to poorly immunogenic carcinomas [28][29].…”
Section: Patient Selectionsupporting
confidence: 85%
“…The abscopal effect was mostly expected during the treatment of these tumors. In our review, remarkable abscopal responses were also seen in other histologic types, such as gastric, esophageal, or pancreatic cancers [17,[21][22]. This observation is consistent with preclinical data, suggesting that the combination of RT and immunotherapy induces effective immune responses to poorly immunogenic carcinomas [28][29].…”
Section: Patient Selectionsupporting
confidence: 85%
“…Recent studies have demonstrated that an abscopal effect can be induced in patients by the combination of radiotherapy and anti-PD1-therapy (nivolumab 63,64 , pembrolizumab 65,66 ), anti-CTLA-4 therapy (Ipilimumab 67 ) and granulocyte-macrophage colony-stimulating factor (GM-CSF) therapy 68 . We previously found 29 that combining Prop with anti-PD-1 in murine tumor models results in a significant improvement in anti-PD-1 efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, some studies suggest that the abscopal effect is relatively rare due to the immunotolerance of the tumor, which results in a reduced systemic immune response. However, treatment with immune checkpoint inhibitors might overcome this immunosuppression, thus converting an immunologically “cold” tumor into a “hot” tumor (171, 172).…”
Section: A Brief Comment On the Abscopal Effect And Its Consequences mentioning
confidence: 99%